Identification of a B cell-dependent subpopulation of multiple sclerosis by measurements of brain-reactive B cells in the blood - Kuerten, Stefanie; Pommerschein, Giovanna; Barth, Stefanie K.; Hohmann, Christopher; Milles, Bianca; Sammer, Fabian W.; Duffy, Cathrina E.; Wunsch, Marie; Rovituso, Damiano M.; Schroeter, Michael; Addicks, Klaus; Kaiser, Claudia C.; et al. (Clinical Immunology, 2014)
B cells are increasingly coming into play in the pathogenesis of multiple sclerosis (MS). Here, we screened peripheral blood mononuclear cells (PBMC) from patients with clinically isolated syndrome (CIS), MS, other non-inflammatory neurological, inflammatory neurological or autoimmune diseases, and healthy donors for their B cell reactivity to CNS antigen using the enzyme-linked immunospot technique (ELISPOT) after 96. h of polyclonal stimulation. Our data show that nine of 15 patients with CIS (60.0%) and 53 of 67 patients with definite MS (79.1%) displayed CNS-reactive B cells, compared to none of the control donors. The presence of CNS-reactive B cells in the blood of the majority of patients with MS or at risk to develop MS along with their absence in control subjects suggests that they might be indicative of a B cell-dependent subpopulation of the disease. © 2014.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Autoimmunity; B cells; Blood; ELISPOT; Multiple sclerosis